The Use of Webtoon to Improve Tenth Grade Students Writing Skill in Descriptive Text at SMA IT Baitul Jannah Bandar Lampung - Adji Wibisono Tansil; Bambang Setiyadi; Anwar Fadila (U-Jet Unila Journal of English Language Teaching, 2026)
ABSTRACT THE USE OF WEBTOON TO IMPROVE TENTH GRADE STUDENTS WRITING SKILL IN DESCRIPTIVE TEXT AT SMA IT BAITUL JANNAH BANDAR LAMPUNG Adji Wibisono Tansil This study investigates the effect of using Webtoon as a learning medium to improve students’ writing skills in descriptive text. The research was conducted using a quantitative pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 21 tenth-grade students at SMA Baitul Jannah Bandar Lampung. Data were collected through writing tests administered before and after the treatment. The assessment focused on five aspects of writing: content, organization, vocabulary, language use, and mechanics. The data were analyzed by using a Paired-Sample t-test through SPSS. The results showed that students’ writing achievement improved, as indicated by the increase in the mean score from 50.00 in the pre-test to 79.33 in the post-test. The significance value was 0.000, which is lower than 0.05 (0.000 < 0.05). This indicates that there was a significant difference in students’ writing skills before and after being taught using Webtoon, so the hypothesis was accepted. In conclusion, the use of Webtoon as a learning medium has a positive impact on students’ writing skills, particularly in descriptive text. It enhances students’ motivation and engagement while helping them develop clearer and more structured writing. Therefore, Webtoon can be considered an effective alternative medium for teaching writing in English classrooms. Keywords: webtoon, descriptive text, writing